Improving performance by innovating and exporting: evidence in argentine industrial firms - Marcel, Lizzie (2020)
The main purpose of this research is to analyze innovating and exporting decisions of Argentinean industrial enterprises, and to determine their joint effect on enterprises’ competitive performance. The learning-by-exporting and self-selection hypotheses, broadly discussed in the literature to explain the innovating and exporting behavior of enterprises, are empirically contrasted. The research is explanatory and the effects of interest are estimated by a Logit model. The sample consists of 315 industrial firms surveyed in 2013 in General Pueyrredon (Argentina), selected through a stratified sampling by branch of activity that included information for the period 2008-2013. The results validate the self-selection, learning through exports, and the joint effect of innovating and exporting on the competitive performance of SMEs. Likewise, they evidence that investment and expenditure in innovative activities contribute to innovation in their industry, and that the programs implemented by the Government are essential for the high performance of SMEs. Industrial differences are also found